Detection of O4 absorption around 328 and 419nm in measured atmospheric absorption spectra - Lampel, Johannes; Zielcke, Johannes; Schmitt, Stefan; Pöhler, Denis; Frieß, Udo; Platt, Ulrich; Wagner, Thomas (Atmospheric chemistry and physics, 2018)
Abstract. Retrieving the column of an absorbing trace gas from spectral data requires that all absorbers in the corresponding wavelength range are sufficiently well known. This is especially important for the retrieval of weak absorbers, whose absorptions are often in the 10−4 range. Previous publications on the absorptions of the oxygen dimer O2-O2 (or short: O4) list absorption peaks at 328 and 419 nm, for which no spectrally resolved literature cross sections are available. As these absorptions potentially influence the spectral retrieval of various trace gases, such as HCHO, BrO, OClO and IO, their shape and magnitude need to be quantified. We assume that the shape of the absorption peaks at 328 and 419 nm can be approximated by their respective neighbouring absorption peaks. Using this approach we obtain estimates for the wavelength of the absorption and its magnitude. Using long-path differential optical absorption spectroscopy (LP-DOAS) observations and multi-axis DOAS (MAX-DOAS) observations, we estimate the peak absorption cross sections of O4 to be (1.96 ± 0.20) × 10−47 cm5 molec−2 and determine the wavelength of its maximum at 328.59 ± 0.15 nm. For the absorption at 419.13 ± 0.42 nm a peak O4 cross-section value is determined to be (5.0 ± 3.5) × 10−48 cm5 molec−2.